Insights into the nano- and microstructures of cementitious materials using synchrotron X-rays - García-Aranda, Miguel Ángel; Gómez-de-la-Torre, María de los Ángeles; Bernal, Susan A.; Provis, John L. (Elsevier, 2026)
Synchrotron X-ray techniques have been extensively applied to characterise the mineralogy of anhydrous cementitious materials, the hydration processes and products in cementitious systems, and the alterations induced by different environmental exposure conditions. However, with changes in cement compositions and performance requirements, and an increased focus on materials design for sustainability, there is now strong emphasis on the use of advanced analytical tools to bring fundamentally based, multi-scale, multi-modal, spatially-resolved and/or time-resolved understanding of the physico-chemical factors influencing cementitious materials in the fluid, hardening and cured states. Beamline-based analysis complements conventional laboratory techniques, bringing unique capabilities to develop high-level insights. Here we provide a critical overview of the application of synchrotron radiation-based techniques to cementitious materials, and the opportunities and research needs to unlock their full potential for their use in future cement materials research, including issues related to handling and processing the very large datasets that can be generated.
Keywords: Cemento - Análisis; Sincrotrones; Synchrotron radiation; Diffraction; Rietveld analysis; Spectroscopy; Tomography; Imaging; Segmentation